The Total Track Inspection - Kaewunruen, Sakdirat; Osman, Mohd Haniff Bin; Rungskunroch, Panrawee (Frontiers in Built Environment, 2019)
Operations of railway business have always placed ‘safety’ as the first priority. Managing ‘public safety’ requires integral risk monitoring and management. The risk monitoring for rail infrastructure management relies on accurate health monitoring and integrated track inspection. Health monitoring of all rail assets have given rise to ‘Big Data’, which have been derived and recorded from on-board monitoring and on-track inspections of both fixed and mobile assets. In this paper, the safety-critical inspections of fixed assets or railway infrastructures have be emphasized in order to obtain the integral insights into track defects, irregularities and deterioration of track geometry and components. This paper highlights the systems-based integration framework of on-board and on-site inspection data for railway track integrity assurance under uncertain settings. The risks and consequences of extreme climates have been considered in order to improve adaptiveness, agility and readiness of the systems-based framework of the total track inspection activities that could underpin and assure track infrastructure integrity and resilience. New challenges in observational field data have been highlighted as the evidences for the necessity for the adaptive systems-based framework of the total track inspection.